Unveiling the Metaverse: Exploring Emerging Trends, Multifaceted Perspectives, and Future Challenges - Mueen Uddin; Selvakumar Manickam; Hidayat Ullah; Muath Obaidat; Abdulhalim Dandoush (IEEE Access, 2023)
The metaverse, an emergent interconnected network that harmoniously merges digital and physical realities, represents a revolutionary paradigm in the computing realm, engendering a nexus of immersive, interactive experiences through user avatars. This new digital landscape, forged by the advancement of immersive technologies like virtual and augmented reality, coupled with the sophistication of artificial intelligence, blockchain, and edge computing, presents diverse prospects from innovative experiential creations to the resolution of complex issues like remote work and virtual social engagement, to remote surgeries, immersive learning and so on. Nevertheless, it confronts obstacles, including privacy, security, equitable access, and ethical concerns, necessitating the construction of robust legal and ethical frameworks for the common good. This research, a comprehensive examination of this burgeoning phenomenon, systematically scrutinizes its underpinning constructs and trailblazing applications via databases such as ScienceDirect, ResearchGate, and IEEE Xplore. It uncovers the metaverse’s incarnations in gaming, social platforms, education, and healthcare, signifying its transformative capacity across these sectors. The exploration underscores the imminent requirement of addressing legal and ethical dimensions as we move towards this novel digital existence, thereby paving the way for future research to architect a secure, efficient, and inclusive metaverse.